Therapeutic hypothermia and the risk of infection: a systematic review and meta-analysis - Geurts, Marjolein; Macleod, Malcolm R; Kollmar, Rainer; Kremer, Philip H C; van der Worp, H Bart (Critical care medicine, 2014)
Observational studies suggest that infections are a common complication of therapeutic hypothermia. We performed a systematic review and meta-analysis of randomized trials to examine the risk of infections in patients treated with hypothermia. PubMed, Embase, and the Cochrane Central Register of Controlled Trials were systematically searched for eligible studies up to October 1, 2012. We included randomized controlled clinical trials of therapeutic hypothermia induced in adults for any indication, which reported the prevalence of infection in each treatment group. For each study, we collected information about the baseline characteristics of patients, cooling strategy, and infections. Twenty-three studies were identified, which included 2,820 patients, of whom 1,398 (49.6%) were randomized to hypothermia. Data from another 31 randomized trials, involving 4,004 patients, could not be included because the occurrence of infection was not reported with sufficient detail or not at all. The risk of bias in the included studies was high because information on the method of randomization and definitions of infections lacked in most cases, and assessment of infections was not blinded. In patients treated with hypothermia, the prevalence of all infections was not increased (rate ratio, 1.21 [95% CI, 0.95-1.54]), but there was an increased risk of pneumonia and sepsis (risk ratios, 1.44 [95% CI, 1.10-1.90]; 1.80 [95% CI, 1.04-3.10], respectively). The available evidence, subject to its limitations, strongly suggests an association between therapeutic hypothermia and the risk of pneumonia and sepsis, whereas no increase in the overall risk of infection was observed. All future randomized trials of hypothermia should report on this important complication.